Extraction of Hibiscus rosa sinensis leaves using ultrasonic water bath in determining the phenolic content / Nor Fazlina Abdul Ghani and Dr Nor Fariza Ismail - Abdul Ghani, Nor Fazlina; Ismail, Nor Fariza (2021)
Hibiscus rosa-sinensis grows at many places around the globe. Hibiscus rosa-sinensis contains numerous classes of auxiliary metabolites, counting flavonoids, anthocyanins, terpenoids, steroids, polysaccharides, alkaloids, amino acids, lipids, and naphthalene group. Different kind of studies show that parts of Hibiscus rosa-sinensis plants possess antioxidant, antimicrobial, antidiabetic, antiulcer, hepatoprotective, antifertility, antigenotoxic and anti-inflammatory properties that help in treatment of many diseases. Therefore, Hibiscus rosa-sinensis plant has been identified as one of many medicinal plants that possesses various potential in therapeutic applications. Bioactive compound extraction on plants done by several methods like conventional method, Microwave Assisted Extraction (MAE) method etc. However, none of the study has been done on extraction of bioactive compounds extracted from Hibiscus rosa-sinensis leaves using Ultrasonic Assisted Extraction (UAE) method. Hence, there is essential to investigate on the benefits of the Hibiscus rosa-sinensis leaves for the future used by using UAE method for extraction. The objectives of this study are to extract bioactive compound extract from Hibiscus rosa-sinensis leaves by using ultrasonic water bath using different solvents like ethanol, methanol, ethyl acetate and acetone and to analyse phenolic profile from the extract. The solvent is chosen based on the polarity due to the presence of hydroxyl group in determining the phenolic compound. Hibiscus rosa-sinensis leaves is prepared by drying at 50°C and pestled before extraction by different solvent. After that, the sample is placed in ultrasonic water bath at different time (5 min, 15 min, 30 min, 45 min, 60 min) and then the solvent is removed by using rotary evaporator. The result shows the highest extraction yield by UAE method is methanol and then followed by ethanol, acetone, and ethyl acetate. After extraction, UV-VIS spectrophotometer was used to determine the phenolic content in Hibiscus rosa-sinensis leaves. Even though methanol has the highest yield of extraction, it is not the best solvent to determine the phenolic content when comparing it with standard calibration curve of Gallic acid. However, as for ethyl acetate, it has the lowest extraction yield but able to determine the phenolic content. As a conclusion, the yield of extraction does not affect the determination of the phenolic content.